A New Paradigm of Education and Potentials of Artificial Intelligence - Mandić, Danimir (Napredak, 2024)
This paper addresses the possibility of using artificial intelligence (AI) in education and establishing rules, restrictions and procedures for the safe use of AI in different fields. In the past two decades, we have been trying to improve educational technology by using multimedia, hypermedia, virtual and extended reality, as well as educational software. It has led to the raised quality of learning, increased dynamics and obviousness of the teaching process, as well as encouraged motivation of students. In the past few years, the possibilities of using AI in education have been researched, particularly in the sphere of personalized learning, more dynamic teaching, as well as complex evaluation of students’ work. The paper analyzes the benefits, challenges and risks in relation to the use of AI in education and emphasizes the importance of maintaining balance between AI and human interaction. It also analyzes the use of robots in education with the aim of encouraging creativity and critical thinking, as well as developing problem-solving skills through the development of algorithm thinking. In the past year, the application of ChatGPT has been intensified in education and that is why it is necessary to define rules and procedures in which this technology would contribute to teaching and learning.
Keywords: artificial intelligence; educational technology; digital competences